RESISTÊNCIA DE GENÓTIPOS DE FEIJÃO-VAGEM AO ATAQUE DE BRUQUÍ-NEOS, EM CONDIÇÕES DE LABORATÓRIO - DALINE BENITES BOTTEGA; CAMILA ALVES RODRIGUES; FLÁVIO GONÇALVES DE JESUS; ANDERSON GONÇALVES DA SILVA; NEI PEIXOTO (Revista Caatinga, 2012)
The aim of this paper was to determine resistance types of snap beans genotypes under infestation of bruchins Zabrotes subfasciatus (Bohemann, 1833) of Acanthoscelides obtectus (Say, 1831) in a no choice and free choice tests. The treatments were arranged in a completely randomized design with four and five replications, respectively. In no choice test, it was evaluated the total number of viable and unviable eggs, dry weight of the consumed food, percentage of emerged insects, weight of insects, longevity of adults and biological cycle of egg to adult. In a free choice test, the number of attracted insects for each genotype and total number of eggs were evaluated. The genotype ARFVI047 presents oviposition non-preference resistance type to Z. subfasciatus. The genotype ARFVI008 presents resistance type of the antibiosis to Z. subfasciatus. The genotypes ARFVI006, ARFVI008 and ARFVI029 present resistance of non-preference for oviposition type to Z. subfasciatus and the genotype HAV 56 black seed presents resistance of non-preference type for feeding of A. obtectus.